Development of a model for the development of technological aspects of innovation management of high-tech enterprises in industry 4.0 - Sazonov, A. A.; Mikhailova, L. V. (AIP conference proceedings, 2024)
The processes of transformation of modern economic systems in order to adapt them to the current market realities involve an increase in the number of requirements in the field of quality management of all innovative and digital activities, as a dominant factor that ensures their sustainable development, and also increases the current level of competitiveness. It is in the current economic realities that innovations in the field of digital technologies play a leading role in the process of creating additional competitive advantages. The authors have developed a multicomponent model for the development of organizational and technological aspects of managing innovative activities of high-tech enterprises, a distinctive feature of the model is its accuracy, the ability to obtain a complete assessment of the various technical, financial and labor resources that an enterprise needs to effectively implement innovative programs. The methodological basis of the research carried out within the framework of the article is built on the fundamental dialectical laws, which consider the innovative activity of an enterprise as a constantly evolving multicomponent system, which, in turn, is subject to the principles of development. The practical significance of the results obtained in the course of the study is to supplement the already existing methodological apparatus for organizing management in the field of innovation. The model proposed by the authors will ensure the algorithmization of technical and functional procedures, make changes to the work of the research mechanism, which will ultimately allow transforming the general outline of innovative behavior within the framework of the implementation of the Industry 4.0 concept.